Effect of COVID-19 vaccination appointment letters on uptake by sociodemographic characteristics : a regression discontinuity analysis in Sweden, December 2020 to September 2021 - Varotsis, Georgios; Hammar, Ulf; Bonander, Carl; Lundmark, Per; Kennedy, Beatrice; Gomez, Maria F. ; 0000-0001-6210-3142; Martinell, Mats; Dyar, Oliver J.; Sarkadi, Anna; Kristiansson, Robert; Svaleryd, Helena; Fall, Tove (European Journal of Public Health, 2025)
Ensuring high vaccination coverage is vital, particularly during a pandemic. While pre-booked appointment letters have shown promise in vaccination campaigns, their effectiveness in specific sociodemographic groups remains to be explored. Our study evaluated the effect of pre-booked appointment letters on COVID-19 vaccine uptake within different sociodemographic groups using a quasi-experimental methodology. In Uppsala County, Sweden, residents born between 1962 and 1971 received pre-booked COVID-19 vaccination letters starting 24 May 2021, while younger residents received SMS prompts for self-booking starting 7 June 2021. Through a regression discontinuity design, we used the intervention cut-off at birth year 1971 to assess the effectiveness of the letters to increase vaccine uptake compared to the SMS campaign. Our analysis included 96 194 individuals born between 1962 and 1981, examining vaccination within 90 days post-eligibility as primary outcome. We investigated effects within sociodemographic groups, assessed household spillover effects, and performed negative control analyses using neighbouring counties. Adults just above the cut-off had an odds ratio of 1.3 (95% CI 1.10-1.53) of being vaccinated than those just below, with a 1.97 percentage point increase (95% CI: 0.45-3.50) from a baseline of 91.95%. The intervention showed effectiveness within most sociodemographic strata. No effects were found in negative control counties, nor were there household spillover effects. Pre-booked appointment letters are effective at boosting vaccination uptake, even in diverse sociodemographic groups. While our findings come from COVID-19 vaccination, they align with evidence from various immunization programs, suggesting that personalized communications can achieve equitable vaccine coverage across different healthcare settings.
Publisher Copyright: © 2025 The Author(s).